Migrações e fluxo escolar da coorte de estudantes de 2008 a 2019, em Minas Gerais - Thiago Zordan Malaguth (2022)
The migration of students is an important phenomenon that may have implications for the educational outcome of children and teenagers. Coleman (1988 and 1990) suggested that social capital outside the family would play an essential role in the construction of individuals' human capital, and migrations could rupture this social capital, leading to a worsening educational outcome of migrants. Few studies have evaluated the influence of migration on individuals' school achievement, especially in the context of developing countries. This master's dissertation aims to analyze the relationship between migrations and school flow of the cohort of students from Minas Gerais enrolled in the 1st grade of secondary school in 2008. Therefore, two guiding questions were elaborated for the work: Is there selectivity related to the school flow in the migration of students? After migration, does the school flow of students become more irregular compared to non-migrant students? This work uses a longitudinal database with school flow information from 2008 to 2019. The strategy used to analyze the relationship between migration and school flow was the comparison between migrants and non-migrants of the proportions of students with a regular school trajectory until the calendar year of the first migration and the promotion rates from the year in which the first migration took place. The analysis indicates a negative relationship between migration and school flow after the movement. The negative variation in the result is observed immediately after the movement and tends to decrease with time. The negative variation is greater for students who migrated for the first time when they were older. Nonetheless, the movements in years corresponding to transitions from elementary to middle school or from middle to high school had a pattern of selectivity and variation different from the other years, especially in the case of transition to high school. The proportion of regular students in the cohort who migrated for the first time in 2016 is 1.24 times that of non-migrants. For these migrants, after the movement, the promotion rate of students who migrated once remained higher than non-migrants.